Associations between mental health, social cognition, and COVID-19 stress among South African university students - Mlomo, Zintle W (Department of Psychology, 2025)
The COVID-19 pandemic has contributed to widespread psychosocial distress, observed in the unprecedented rise in symptoms of common mental disorders (CMDs), including depression, anxiety and post-traumatic stress disorder (PTSD). This surge in mental health complications has been reported across all populations globally, most notably among university students, who are already a vulnerable cohort to CMDs, including PTSD. As integral socio-cognitive mechanisms of emotional regulation and interpersonal functioning, cognitive and affective empathy may potentially protect against or aggravate symptoms of CMDs, including PTSD, respectively. However, there is a scarcity of South African literature exploring this relationship, and relatively few South African studies have investigated students' mental health in the context of the COVID-19 pandemic. The current study employed a descriptive, cross-sectional design and aimed at evaluating the relationship between sociodemographic variables, pandemic-related-stress and exposure, mental health and cognitive and affective empathy, and explore the potentially moderating role of empathy. 534 undergraduate and postgraduate students from the University of Cape Town (UCT) were recruited using convenience sampling to participate in an online survey. Participants were administered a brief demographic questionnaire, the Kessler Psychological Distress Scale (K 10), the Beck Depression Inventory-Second edition (BDI-II), the Beck Anxiety Inventory (BAI), PTSD-Checklist for DSM-5 (PCL-5), the Pandemic Stress Questionnaire (PSQ) and the Interpersonal Reactivity Index (IRI). Overall, the results showed that female biological sex, self-reported history of psychological diagnosis, and earlier year of study were significant sociodemographic predictors of higher symptoms of CMDs, including PTSD. Furthermore, the results showed positive associations between mental health outcomes and affective empathy, and further provided significant evidence of the potentially moderating role of affective and cognitive empathy in the relationship between pandemic-related stress and exposure and mental health outcomes. These findings contribute to the current research gap on empathy and mental health in South Africa and provide further insight into the role of cognitive and affective empathy in relation to mental health in the context of stressful environmental factors. Further research should be conducted to explore additional factors and mechanisms that could explain individual mental health and social cognition in relation to stressful environmental factors